Positive psychology at work - the science and art of thriving - Baker, R (Bodleian Libraries, University of Oxford, 2022)
This session will explore how we can apply the science and thinking from the fields of positive psychology and behaviour science to make work happier, healthier and more productive. Participants will learn actions they can take to influence their own flourishing, energy and performance at work and how to support and encourage the wellbeing of others. The session will be informative, practical and fast-paced (and fun). The focus will be on sharing ideas in a clear way that participants can then share, explain and utilise with their colleagues in the practical challenges they are facing.